2023
DOI: 10.1002/ece3.9875
|View full text |Cite
|
Sign up to set email alerts
|

What role do dauciform roots play? Responses of Carex filispica to trampling in alpine meadows based on functional traits

Abstract: To adapt to environmental diversity, all plants face the challenge to balance their competing needs with limited resources. As a result, diverse life strategies are shaped, which can be quantified by multiple functional trait dimensions (Reich, 2014). Functional traits of plants usually show a common pattern of co-variation rather than varying independently, through which plants adjust their strategies of resource

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 65 publications
2
5
0
Order By: Relevance
“…In fact, while having the same response of belowground C to the intensifying degradation, P. viviparum and C. filispica without dauciform roots also showed a similar response to dauciform roots: as the proportion of dauciform roots increased, their position on the economic spectrum was both biased in a resource-conservative direction ( Figure 6 ), while individuals with dauciform roots did not have the same tendency. Our result is consistent with an earlier study showing that individuals with dauciform roots were proven to have more resource-acquiring traits after human trampling ( Fan et al., 2023 ). Species with resource-acquisitive strategies tend to increase as disturbance intensified ( Huang et al., 2021 ), and owing to the resource acquisition of dauciform roots contributing to the P-dissolution to ease the disturbance, all the other neighbouring plants remained resource-conservative.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, while having the same response of belowground C to the intensifying degradation, P. viviparum and C. filispica without dauciform roots also showed a similar response to dauciform roots: as the proportion of dauciform roots increased, their position on the economic spectrum was both biased in a resource-conservative direction ( Figure 6 ), while individuals with dauciform roots did not have the same tendency. Our result is consistent with an earlier study showing that individuals with dauciform roots were proven to have more resource-acquiring traits after human trampling ( Fan et al., 2023 ). Species with resource-acquisitive strategies tend to increase as disturbance intensified ( Huang et al., 2021 ), and owing to the resource acquisition of dauciform roots contributing to the P-dissolution to ease the disturbance, all the other neighbouring plants remained resource-conservative.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have found that sedges with DRs have relatively less belowground biomass allocation and suggested that DRs may ease the limitation of belowground resources so that resources can be invested in the growth of aboveground parts (Gusewell & Schroth, 2017). The results of the 2‐week recovery showed that the number of DRs was positively proportional to the overall leaf size of C. filispica (Fan et al., 2023), but since the morphology was not measured separately in individuals with or without DRs, the exact object of effect could not be determined. This study further found that both the leaf area of individuals with and without DRs showed a positive correlation with the number of DRs (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Trampling leads to a shift in competitiveness from sensitive species to more tolerant ones (Miehe et al., 2019). With the increasing grazing disturbance, grasses and legumes on Tibetan plateau meadows are gradually replaced by sedge (Guo et al., 2019), which has been found to have a strong short‐term resistance to trampling, with no significant decrease in cover as the trampling intensity increases (Fan et al., 2023). As for this experiment, 1 year after trampling, the proportion of plants with DRs increased with trampling intensity, although the difference was not significant (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations